Eclissi e noviluni. Due note a Sen. ‘nat.’ VII - Daniele Pellacani (Griseldaonline)
On the basis of lexical and stylistic considerations, a new interpretation of two Senecan passages (nat. vii 1, 3 and vii 25, 3) is proposed, defending the transmitted text.